Pelatihan Teknik Menyusun Laporan Keuangan Untuk UMKM Agribisnis - Ilsan, Mais; Salim, Muhammad; Husain, Tsalis Kurniawan (University of Islam Malang, 2020)
The goal to be achieved in this service program is to help compile and make financial statements CV. Kasih dan Sayang. Specific targets to be completed are knowledge and skills in preparing and formatting financial statements. The problem in preparing financial statements is knowledge and skills in the recording of business finances. Therefore, the challenges in this target group need to be overcome by increasing knowledge and training in making financial statements that are easy and helping financial records for partners. The method that will be used in this service program is participation method. CV. Kasih dan Sayang were given financial statement training. The results of this community service activity are trainees who are able to provide training materials that are supported by using financial statements formats in the form of MS. Excel is in accordance with the case of business transactions. In addition, the financial statement format is in the form of an MS. Excel will tidy up and make it easier to make business financial statements.